Seychelles : Third Review Under the Extended Arrangement and Request for Modification of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Seychelles' Third Review Under the Extended Arrangement and Request for Modification of Performance Criteria (PC). All PCs for end-June 2015, the program's third test date, were met. Based on preliminary data, all the third-quarter indicative targets were also met. The structural agenda is proceeding, albeit with some delays. Growth for 2015 has been revised upward to slightly more than 4 percent. Presidential elections are taking place during December 3-5. The IMF staff recommends completion of the third review under the Extended Arrangement and modification of the PCs for end-December 2015.